Inventarisasi Jenis Belalang di Agroekosistem Zea Mays L. Kecamatan Karanggayam - Bagas Prakoso; Fatwa Aji Kurniawan (Jurnal READ (Research of Empowerment and Development), 2021)
This research aims to determine the types of grasshoppers and the diversity index of maize Zea mays L.) agroecosystems in Karanggayam district. This research was conducted using a field survey method. The parameters observed at each location included vegetation diversity, grasshopper collection and direct observation of orthoptera locusts. Samples were taken from the Zea mays L. agroecosystem and repeated three times. The study was conducted in June - August 2019. The results of this study were found as many as 346 individuals, four species consisting of Valanga nigricornis (Burmeister), Gesunola mundane (Walker), Atractomorpha crenulata, and Oxya hyla intricate (Stal). Three genera consisting of Valanga, Gesunola, and Oxya belong to the Acrididae family, while one genus, namely Atractomorpha, is included in the Pyrgomorphidae family. Shannon-Weiner (H') insect diversity index at station 1 is 1.124 (moderate), station 2 of 0.979 (low), station 3 of 0.449 (low), station 4 of 1.213 (moderate), station 5 of 0.884 (low) and station 6 of 1.035 (moderate).